“La vulnerabilidad financiera a través de un análisis de la rentabilidad, liquidez y suficiencia patrimonial de los Bancos Privados en el Ecuador durante el periodo 2017- 2023” - González Armijos, Gabriela Salome (2024)
Volatility in financial markets and the adoption of expansionary monetary policies have created an environment of uncertainty that challenges the resilience of banking institutions, making them more vulnerable, in the case of Ecuador, according to the Central Bank of Ecuador private banks faced a severe economic contraction in 2020 which exacerbated credit and operational risks. In this sense, the general objective of the present research is to evaluate financial vulnerability through the analysis of profitability, liquidity and equity adequacy of private banks in Ecuador during the period 2017-2023, through a statistical and econometric study of panel data in order to establish early warning mechanisms for financial crisis risks. In this context, with data from the monthly series bulletins of the Superintendency of Banks of Ecuador, generalized least squares (GLS) models, short and long term cointegration and, Dimitrescu and Hurlin causality test were applied. The main findings revealed that there is a significant trend and a negative effect on the variables profitability, liquidity and capital adequacy, that is, as these indicators increase, the vulnerability of banks decreases. In addition, the variables analyzed show cointegration in the short term, although not in the long term, and there is also a bidirectional causal relationship in most of the variables on financial vulnerability. Finally, in order to establish prevention mechanisms, it is recommended to strengthen regulatory supervision by adopting Basel III standards, promote transparency in bank information and encourage good corporate governance.